Metabolomics reveal physiological changes in mayfly larvae (Neocloeon triangulifer) at ecological upper thermal limits. (August 2017) - Chou, Hsuan; Pathmasiri, Wimal; Deese-Spruill, Jocelin; Sumner, Susan; Buchwalter, David B.
Graphical abstract: Highlights: Effects of short-term, sublethal thermal challenge on Neocloeon triangulifer were examined. Metabolomics data indicate thermal challenge greatly influences energetic pathways. Limited evidence of anaerobic metabolism were found in thermally challenged mayflies. Abstract: Aquatic insects play critical roles in freshwater ecosystems and temperature is a fundamental driver of species performance and distributions. However, the physiological mechanisms that determine the thermal performance of species remain unclear. Here we used a metabolomics approach to gain insights into physiological changes associated with a short-term, sublethal thermal challenge in the mayfly Neocloeon triangulifer (Ephemeroptera: Baetidae). Larvae were subjected to a thermal ramp (from 22 to 30 °C at a rate of 1 °C/h) and metabolomics analysis (both Nuclear Magnetic Resonance (NMR) Spectroscopy and Gas Chromatography coupled Time-of-Flight Mass Spectrometry (GC-TOF-MS)) indicated that processes related to energetics (sugar metabolism) and membrane stabilization primarily differentiated heat treated larvae from controls. Limited evidence of anaerobic metabolism was observed in the heat treated larvae at 30 °C, a temperature that is chronically lethal to larvae.